2015
DOI: 10.1152/jn.00292.2014
|View full text |Cite
|
Sign up to set email alerts
|

Resting state arousal and functional connectivity in autism spectrum disorder

Abstract: Brain 137: 153-171, 2014) demonstrated that resting state electrodermal activity is correlated with different patterns of brain activity in subjects with autism spectrum disorder (ASD) than in typical controls. These results are considered in light of theories of atypical arousal in ASD.arousal; autism; skin conductance; functional connectivity AROUSAL REFERS TO PHYSIOLOGICAL states and behaviors associated with an alert state. Atypical arousal has been hypothesized to explain some of the symptoms of autism sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…heart rate variability), electrodermal activity, and pupil size, both at rest and during pre-task baseline periods. We did not include evidence from studies measuring CNS arousal or cortisol/ neurotransmitters, because indices of arousal at CNS are debated, and some of this evidence has been reviewed (Berman et al, 2015;Kleberg, 2015;Wang et al, 2013).…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
“…heart rate variability), electrodermal activity, and pupil size, both at rest and during pre-task baseline periods. We did not include evidence from studies measuring CNS arousal or cortisol/ neurotransmitters, because indices of arousal at CNS are debated, and some of this evidence has been reviewed (Berman et al, 2015;Kleberg, 2015;Wang et al, 2013).…”
Section: Purpose Of This Reviewmentioning
confidence: 99%
“…According to other current theories, atypical regulation of arousal could cause impairment in attention, another symptom commonly associated with ASD (Orekhova & Stroganova, 2014). A series of current studies of autonomic dysfunctions in ASD were reported in the literature showing drastically increased interest in the investigation of autonomic system functioning abnormalities in children with autism (Benevides & Lane, 2015;Cohen, Masyn, Mastergeorge, & Hessl, 2015;Kleberg, 2015;Kushki et al, 2013Kushki et al, , 2014Patriquin, Lorenzi, & Scarpa, 2013;Smeekens et al, 2015). As noted by Rees (2014), there is an urgent need to recognize the importance of the ANS in pediatrics, not limited to neurodevelopmental disorders.…”
Section: Review Of Autonomic Dysfunctions In Autism Cardiac Activitymentioning
confidence: 99%
“…Furthermore, children with ASD demonstrate dampened HR reactivity, unusually small deceleratory HR responses, and generally low cardiac reactions to auditory stimulation including socially relevant speech, phrases, and tones (Corona, Dissanayake, Arbelle, Wellington, & Sigman, 1998;Palkovitz & Wiesenfeld, 1980;Zahn, Rumsey, & Van Kammen, 1987). Kleberg (2015) emphasized that atypical autonomic arousal has been used to explain some of the core symptoms of ASD. In effect, it has been hypothesized that either elevated or attenuated tonic arousal was a causal factor behind some of the core autism symptoms, such as repetitive behaviors (Hirstein et al, 2001;Toichi & Kamio, 2003;Toichi et al, 1999) and avoidance of social interaction (Rogers & Ozonoff, 2005).…”
Section: Review Of Autonomic Dysfunctions In Autism Cardiac Activitymentioning
confidence: 99%